Research handbook on civil-military relations - Croissant, Aurel; Kuehn, David D.; Pion-Berlin, David (Elgar handbooks in political science, 2024)
"Bringing together leading international scholars, this comprehensive Research Handbook analyses key problems, subjects, regions and countries in civil-military relations. Showcasing cutting-edge research developments, it illustrates the deeply complex nature of the field and examines important topics in need of renewed consideration. Arranged in five thematic sections, chapters explore the role of armed forces in politics and society, the missions and roles of militaries, and crucial issues of control, compliance and effectiveness. Contributors present theoretically informed and empirically applied research asking novel questions and examining cutting-edge solutions to ongoing problems in the field. They showcase the wide range of research methodologies and meta-theoretical traditions in civil-military relations, spanning structuralism, behaviouralism, institutionalism, and constructivism. Ultimately, the Research Handbook is a timely insight into the contemporary role of militaries, for example in democratisation and autocratisation processes and deployment during natural disasters and pandemics. The Research Handbook on Civil-Military Relations will be an invaluable resource for students and scholars of military, security, and strategic studies, as well as comparative politics and military sociology. It will also be an important read for policy-makers seeking to better understand the role of the military in society"